Phytochemical Arsenal: Understanding Plant Defense Mechanisms Against Nematodes - Jasrotia, Shivam; Kumar, Ajay (Bentham Science Publishers, 2025)
This book explores the complex interactions between plants and parasitic nematodes, with a particular focus on the natural chemical defenses plants deploy against these agricultural pests. As nematode infestations continue to cause major crop losses globally, this book addresses the urgent need for sustainable, eco-friendly alternatives to synthetic pesticides. The book comprises eight in-depth chapters, examining the biochemical and physiological roles of phytochemicals in plant defense, their biosynthesis, modes of action, and the influence of environmental conditions on their efficacy. It also assesses current challenges related to the application of these natural compounds in practical nematode control strategies. Drawing from advances in plant biology, molecular science, and agronomy, the book offers a consolidated view of recent developments in the field. Key features: Analyzes plant-nematode interaction dynamics Details classes and mechanisms of defense-related phytochemicals Explores biosynthetic pathways and environmental influences Examines potential for biopesticide development and integrated management Highlights research gaps and future directions.